Practical approaches to biological inorganic chemistry - Crichton, Robert R.; Louro, Ricardo O. (UK: Elsevier, 2020)
"Practical Approaches to Biological Inorganic Chemistry, Second Edition, reviews the use of spectroscopic and related analytical techniques to investigate the complex structures and mechanisms of biological inorganic systems that contain metals. Each chapter presents an overview of the technique, including relevant theory, a clear explanation of what it is, how it works, and how the technique is actually used to evaluate biological structures. New chapters cover Raman Spectroscopy and Molecular Magnetochemistry, but all chapters have been updated to reflect the latest developments in discussed techniques. Practical examples, problems and many color figures are also included to illustrate key concepts."--
Includes bibliographical references and index.
Keywords: Bioinorganic; Chimie bio-inorganique.; Bioinorganic chemistry